Mainstreaming the social indicators of the seafood stewardship index for greater equity in the Asian seafood and aquaculture industry - Dio Herdiawan Tobing (Asian Development Bank Institute (ADBI), 2023)
This paper seeks to outline the power of benchmarking to influence social transformation in the fisheries industry in contributing to the realization of ocean equity. It will do so by drawing on the experience of the Seafood Stewardship Index of the World Benchmarking Alliance (WBA), which assesses the 30 most powerful seafood industries on their pathways towards sustainability from the equity angle, which aims to ensure that the distribution of ocean wealth is accessible for workers and coastal communities whilst protecting their rights by minimizing harm inflicted on them. With the existence of cases of modern slavery in the fisheries industry, enhancing the quality of reporting has become an important reason for businesses to ensure that the supply chain process does not procure from illegal fishing and/or is not farmed by trafficked workers. This paper explains the above objectives by conceptualizing the scope and definitions of ocean equity, exploring the trends and insights based on the WBA's Seafood Stewardship Index's (SSI) scoring of the world's 30 most influential seafood companies, and further showcases how engagement with key actors is useful in driving changes among seafood companies. Finally, the author draws on policy recommendations that seek to incentivize actors with a view to achieving better social outcomes in the ocean.
Keywords: F660; 330; benchmarking; business and human rights; seafood industry; ocean equity